2011
DOI: 10.1080/14697017.2011.564591
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Change and Identity Work In the Swampy Lowland

Abstract: Our aim is to examine intractability in relation to processes of change. Drawing upon data gathered from workshops, documentary sources and follow-up interviews, we identify an apparent contradiction between accounts of the self as change-oriented and subsequent inaction. We argue that the dominant metaphor typically used to explain such contradictions -barriers to changeprovides an inadequate characterization of change inactivity. We present an alternative way of thinking about change in which the issue of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In recounting stories of 'resistance to change', most interviewees framed this as a perfectly normal response, recognizing the need to create time and space for people to engage with change on their own terms, and acknowledging their own role in seeking to understand how others related to change. Many interviewees made direct or indirect references to identity, and 'resistance to change' was framed less as an Leading change 17 obstacle and more as a call to dialogue (Beech et al, 2011;Caldwell, 2013;van Dijk & van Dick, 2009;Ford, Ford, & Amelio, 2008;Johansson & Heide, 2008;Thomas & Hardy, 2011). There was a general and explicit acknowledgement that top-down linear approaches to change were usually ineffective.…”
Section: Emergent Changementioning
confidence: 96%
See 1 more Smart Citation
“…In recounting stories of 'resistance to change', most interviewees framed this as a perfectly normal response, recognizing the need to create time and space for people to engage with change on their own terms, and acknowledging their own role in seeking to understand how others related to change. Many interviewees made direct or indirect references to identity, and 'resistance to change' was framed less as an Leading change 17 obstacle and more as a call to dialogue (Beech et al, 2011;Caldwell, 2013;van Dijk & van Dick, 2009;Ford, Ford, & Amelio, 2008;Johansson & Heide, 2008;Thomas & Hardy, 2011). There was a general and explicit acknowledgement that top-down linear approaches to change were usually ineffective.…”
Section: Emergent Changementioning
confidence: 96%
“…This sensemaking process is social (Weick et al, 2005) and the development of identity is therefore a socially constructed process (Beech, Kajzer-Mitchell, Oswick, & Saren, 2011;Reissner, 2010), a reflexive narrative in which people experiment with different identities through talking to others as well as themselves. Gover and Duxbury (2012) outlined a 'faultline theory' that describes how coalitions develop within organizations on the basis of homogeneity and heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…In this complex domain, conflicting identities may be seen as a 'thorny' issue for institutions. Beech et al (2011) use another metaphor, the 'swampy lowland', to describe the messy nature of this issue. However, alternative options do exist.…”
Section: Researching Academic Identitymentioning
confidence: 99%
“…We note that other identity studies (for example, Beech et al 2011;Green and Little 2013) and leadership studies have effectively used metaphors. Crossman and Crossman (2011) identified that authors frequently used metaphors to describe and explain follower behaviour.…”
Section: Limitations Of Our Study and Of Using Metaphorsmentioning
confidence: 99%